Gorham's disease of mandible - a rare case presentation in pediatric patient - Santanu Mukhopadhyay; Abira Chattopadhyay; Raja Bhattacharya; Ushapati Roy (Wolters Kluwer Medknow Publications, 2016)
Gorham's disease or vanishing bone disease is a rare, progressive musculoskeletal disorder characterized by resorption of bone matrix, and later replaced by fibrous connective tissue. The disease has no specific predilection for age, gender, or race. The most common sites of involvement are the shoulder and pelvic bones. To date, nearly 50 cases of Gorham's disease with maxillofacial involvement have been reported in the literature. The etiology of Gorham's disease is not known, clinical features are variable, and prognosis is generally good unless vital structures are involved. Due to the rarity of the condition, no definite treatment protocol exists for this disorder. Here, we described a pediatric case of Gorham's disease with mandibular involvement.